Acute Kidney Injury in Neonates: A Single-Center Experience - Khudhair, Ali A.; Naama , Khalid Z.; Khaleel , Ammar K.; Saadi , Yasir I. (Journal of the Faculty of Medicine Baghdad, 2023)
Background: Neonatal intensive care unit infants frequently experience acute kidney damage. Estimates of the prevalence of acute kidney vary depending on the definitions used. In Iraq, studies addressing the prevalence and risk factors of acute kidney injury in this age group are scarce, none of which has implicated the KDIGO diagnostic and staging criteria.Objectives: To describe the prevalence, demographics, risk factors, etiology, and staging of acute kidney injury using KDIGO criteria in the Neonatal intensive care unit and correlate these findings with patient outcomes.Methods: A retrospective study was conducted in the Neonatal Intensive Care Unit/ CWTH/ Medical City Complex/ Baghdad during the period from the 1st of August 2019 to the 15th of January 2020.  All neonates diagnosed with acute kidney injury according to KDIGO –classification 2012 and admitted to the neonatal intensive care unit were included in this study. Demographics, clinical staging, and investigations were retrieved from patients' notes.Results: The prevalence of acute kidney damage was 7.2%.  The mean gestational age of the patients was 36.8 ± 2.9 weeks, 58% of them were full-term, with a male-to-female ratio of 1.40:1. Stage I patients represented 35.1%, 43.2% were stage 2, and 21.6% had severe stage 3. Acute kidney injury-related mortality was 35.1%. The term female sex, high birth weight, and age younger than seven days at diagnosis predicted a bad prognosis. Vaginally delivered, stage III acute kidney injury-KDIGO, and peritoneal dialysis patients had the worst outcomes. Asphyxia was a major cause of acute kidney injury (P=0.001). High blood urea (P=0.01), low PH (P=0.009), low HCO3 (P=0.001), low WBC count (P=0.001), and low platelet count (0.001) were associated with unfavorable outcomes.Conclusions: The prevalence of acute kidney injury, according to KIDGO diagnostic and staging criteria, is 7.1%. Asphyxia, female gender, and vaginal deliveries are variables associated with poor prognosis in addition to advanced illness stage and laboratory indicators.